Evaluación de riesgos psicosociales en el área administrativa del grupo MB Mayflower-Buffalos, de octubre 2015 a marzo 2016 - Enríquez Pupiales, Diana Isabel (2016)
The aim of this work is the evaluation of Psychosocial Risks in the Administrative area akin to build MB GROUP possible action steps to preserve their culture environment as pleasant and harmonious work. In this paper we analyzed the psychosocial risks present in the MB Group through the application of test FPSICO 3.0, same as measures nine dimensions. TT Working time P / S Participation and Oversight AU Autonomy ITC Interest worker / Compensation CT Workload DR Performance Role DP Psychological Demands RAS Relationships and social support VC Variety / Work content The analysis of results of Fpsico 3.0 method to workers grouped by occupational groups depending on their position in the company. For the execution of this diagnosis has been made the following steps: a) Diagnosis of the situation in the organization b) Acceptance of the project by the group management Mayflower MB-Buffalos c) Measurement of the factors through the tool. d) Tabulation and analysis of the results obtained. e) Awareness of the results. f) Proposal for control and prevention of critical points. Similarly we proceeded with the systematization of practical experience considering the parameters given by the Salesian Polytechnic University format. The format contains the methodological steps that must be taken into account for the implementation of the report of systematization. The work allowed us to establish levels of psychosocial risk among prevalent as psychosocial risk factors ITC interest by the worker in his work area and CT workload, which are present on the staff of the company.